Status of research on prediction models for severity in confirmed Covid-19 patients - Maicel Eugenio Monzón-Pérez; Lizet Sánchez-Valdés; Elizabeth Rieche-Gómez; Agustín Lage-Dávila (Revista Habanera de Ciencias Médicas)
Introduction: Previous knowledge in the scientific literature on clinical prediction models in patients with COVID-19 may be useful for the development of new research.